Adolescent Obesity: Understanding Psychological Impacts And Knowledge Gaps In Urban India - Mudhol, Basavaraj; Jha, Pooja; Rastogi, Muskan; Vijimol, Vijimol; Jyoti, Jyoti; Rakhi, Rakhi (Journal of Neonatal Surgery, 2025)
Adolescent obesity has emerged as a global health concern, with significant physical and psychological implications. This study aimed to assess adolescents' knowledge regarding the psychological impacts of obesity in a selected pre-university college in Bangalore, with a view to developing an information guide sheet. Using a descriptive research design, data were collected from 455 adolescents (272 boys and 183 girls) aged 16–17 years through a structured knowledge questionnaire comprising 40 items. The questionnaire assessed four key areas: basic concepts of obesity, psychological impacts, body dissatisfaction, and poor psychosocial adjustment. Findings revealed that 56% of participants had inadequate knowledge, 44% had moderate knowledge, and none demonstrated adequate knowledge about the psychological impacts of obesity. The mean knowledge score was 41.4%, with the highest scores in basic concepts of obesity (46.3%) and the lowest in depression and poor psychosocial adjustment (37.8%). Significant associations were observed between knowledge levels and variables such as age, gender, place of residence, and dietary patterns. Older adolescents, females, and those with mixed dietary patterns had better knowledge scores. The results underscore the urgent need for targeted educational interventions to improve adolescents' understanding of obesity and its psychological consequences. Such efforts are essential to promote healthier behaviors, improve mental well-being, and reduce the burden of obesity-related complications. This study highlights the critical role of health education in addressing the dual burden of physical and psychological challenges associated with adolescent obesity